2019
DOI: 10.1016/j.kint.2018.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Management and treatment of glomerular diseases (part 2): conclusions from a Kidney Disease: Improving Global Outcomes (KDIGO) Controversies Conference

Abstract: In November 2017, the Kidney Disease: Improving Global Outcomes (KDIGO) initiative brought a diverse panel of experts in glomerular diseases together to discuss the 2012 KDIGO glomerulonephritis guideline in the context of new developments and insights that had occurred over the years since its publication. During this KDIGO Controversies Conference on Glomerular Diseases, the group examined data on disease pathogenesis, biomarkers, and treatments to identify areas of consensus and areas of controversy. This r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
96
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(102 citation statements)
references
References 186 publications
(203 reference statements)
0
96
0
6
Order By: Relevance
“…Cyclophosphamide is still a commonly used induction therapy for class III and IV LN [8,9]. Our results suggest that in proliferative LN (including class III/III+V, IV/ IV+V LN) the levels of plasma ADMA in patients in complete remission after treatment with cyclophosphamide as induction therapy were significantly lower than those in those patients with noncomplete remission.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Cyclophosphamide is still a commonly used induction therapy for class III and IV LN [8,9]. Our results suggest that in proliferative LN (including class III/III+V, IV/ IV+V LN) the levels of plasma ADMA in patients in complete remission after treatment with cyclophosphamide as induction therapy were significantly lower than those in those patients with noncomplete remission.…”
Section: Discussionmentioning
confidence: 61%
“…A large number of LN patients will progress to chronic kidney disease (CKD) and about 10% patients will develop end-stage kidney disease (ESRD) despite the improvements immunosuppressive therapy [5,6]. One of the strategies to improve the outcome of LN and reduce treatment-related toxicity is to serially evaluate renal disease activity following that initial therapy, which would allow early optimization of immunosuppression [7][8][9]. Unfortunately, current laboratory parameters, including anti-dsDNA, C3, proteinuria, and estimated glomerular filtration rate (eGFR), are insufficient to predict the histological classification of LN and monitor the treatment response.…”
Section: Introductionmentioning
confidence: 99%
“…Current standard treatment of patients with GPA, as stated by most recent recommendations from the Kidney Disease: Improving Global Outcomes (KDIGO) [18], and the European league Against rheumatisom (EULAR) in conjuction with the European renal Association -European Dialysis and transplant Association (ERA-EDTA) [19], includes induction of remission by combination immunosuppressive therapy with high dose Glucocorticoids and either cyclophosphamide or rituximab, which are both equally effective in achieving remission in up to 75% of patient, followed by maintenance therapy for prolonged but variable periods of time and up to 2 years in some patients, with usually a single immunosuppressive agent such as azathioprine or Rituximab to maintain disease activity in remission with the goal of decreasing the incidence and severity of relapsing GPA [20,21]. Mycophenolate mofetile (MMF) and methotrexate has also been used but less commonly in maintenance therapy of patient with GPA.…”
Section: Discussionmentioning
confidence: 99%
“…The guidelines published by the Kidney Disease: Improving Global Outcomes (KDIGO) indicated that angiotensinconverting-enzyme inhibitor (ACEI)/angiotensin receptor blockers (ARB) and corticosteroids were recommended for IgAV-N patients based on the clinical manifestations instead of pathological indicators, and the combination therapy of immunosuppressants and steroids is under debate (4)(5)(6). Emerging studies have demonstrated that the usage of immunosuppressants is significantly correlated to clinical remission of IgAV-N (7,8).…”
Section: Introductionmentioning
confidence: 99%